A.A.B. Sutedja File: Gubernur Bali Pertama dalam Lipatan Sejarah - Slamat Trisila (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractThis paper reveals a portion of political chapter AA Bagus Sutedja of Puri Negara, a royal household in Jembrana, West Bali. Sutedja was the first governor of Bali, the provincial island officiated in 1959, which previously had been partof the Lesser Sunda Island Province. In this article we learn Sutedja’s short, yet sky rocketing political career from a low level governmental official and then built his own way to bethe island first governor. His appointment as the governor wasthe result of then President Soekarno’s political scenario in implementing the policy of the central government in Jakarta.When the 1965’s political tragedy struck in Jakarta that topple the president, Sutedja suffered similar fate. The governor notonly lost his position, but was tragically kidnapped and was believed to have been killed. Till these days his where-aboutremains a mystery in Bali’s dark history.